Mathematical logical intelligences as a predictor of mathematics learning outcomes - Fadhila Kurnia Estri; Ibrahim Ibrahim (STKIP PGRI Banjarmasin, 2021)
The purpose of this research was to determine the prediction of student learning outcomes based on mathematical logical intelligence and spatial visual intelligence. This research uses a quantitative approach, a type of correlational research. That held at 16th state junior high school Yogyakarta. The used sample is 36 students. The used sampling method is cluster random sampling. The used instrument is a scale of mathematical logical intelligence and spatial visual. The data analysis technique for regression analysis is done with SPSS 25. The results of the research prove that logical mathematical intelligence and spatial visuals are predictors of mathematics learning outcomes for Grade VIII students of SMP Negeri 16 Yogyakarta.